Outcome of children born to epileptic mothers treated with carbamazepine during pregnancy. Issue 6 (December 1996) - Ornoy, A; Cohen, E
Abstract : AIM: The purpose of the study was to assess whether there was an increased rate of congenital anomalies or significant developmental delay in infants of women with epilepsy who had been treated with carbamazepine during pregnancy. METHODS: 47 children were studied, aged 6 months-6 years, who were born to 37 epileptic mothers on carbamazepine monotherapy (group A). All children had a complete physical and neurodevelopmental assessment by a developmental paediatrician, and 41 a complete psychological evaluation. They were compared with 47 children of similar socioeconomic status (group B). RESULTS: Six of the 47 children in group A had typical facial features of 'carbamazepine syndrome'. The average cognitive score of children in group A was significantly lower than in group B. This was mainly because all six children with carbamazepine syndrome had a development quotient or intelligence quotient below 90. There were no differences between the two groups in physical growth or in the rate of major anomalies. Two children in group A had cleft palate but in each case this was found in a parent as well. CONCLUSIONS: In utero exposure to carbamazepine may result in 'carbamazepine syndrome' characterised by facial dysmorphic features and mild mental retardation. Prevalence of carbamazepine syndrome does not seem to be related to the dose of carbamazepine or the presence of maternal convulsions. It may depend upon heredofamilial factors that have yet to be defined. One possible factor is decreased activity of the enzyme epoxide hydrolase with resulting increased concentrations of carbamazepine epoxide which may be teratogenic.